The Process of Mary Lennox's Personality Transformation in Frances Hodgson Burnett's The Secret Garden (1911) (English Language and Literature (JELL), 2026)
This article examines the personality transformation of the main character in The Secret Garden (1911) by Frances Hodgson Burnett from being spoiled, selfish, and stubborn to becoming more independent, environmentally aware, and capable of objective thinking, through Sigmund Freud’s psychoanalytic theory of the id, ego, and superego. Using a qualitative descriptive design with close reading, this study identifies textual evidence reflecting the character’s inner conflict and transformation, with data categorized into the id as instinctual drive, the ego as rational control, and the superego as moral awareness. The analysis reveals that the character’s early behavior is dominated by the id, marked by anger, selfishness, and isolation; however, as she builds relationships and connects with nature, the ego begins to balance her impulses with reason, followed by the emergence of the superego, reflected in her empathy and sense of morality, indicating her psychological growth. The study concludes that The Secret Garden portrays a process of emotional healing and personal maturity achieved through interaction, environment, and self-reflection.
Keywords: Psychoanalysis, Freud, id- ego superego, character transformation, The Secret Garden